Enhancing participation in Codex activitives : (FAO, 2005)
This training package has been developed to enhance countries' participation in the Codex process. It explains the organization and operation of Codex and the scientific basis for its work, and provides guidance on developing national Codex structures and activities. The information is presented in modules, with visual aids and practical exercises. A CD-ROM provides the visual aids in electronic format and relevant reference material. The training package is equally useful as a practical reference guide or those involved in Codex, but not directly involved in training.